Effects of mergers on network models of the financial system - Daniel Nevermann; Lotta Heckmann (Deutsche Bundesbank, 2023)
Despite the ongoing consolidation trend in the banking industry and the attention some mergers (in particular between large banks) have been receiving, there is no consistent picture of the impact of mergers on the stability of the financial system. In this paper, we aim to provide a universal framework to study the generic effect of mergers and acquisitions on the resilience of financial systems based on different network models. We investigate the impact of a wide variety of model assumptions, e.g. connectivity, contagion channel and the merger process, on different static and dynamic stability measures. We provide a range of theoretical results highlighting the mechanisms that influence systemic risk in consolidated financial systems. Our main finding is that merger activities can stabilize or destabilize the modelled financial network, depending on various details such as the connectivity of the network and the assumed merger process. Merger activities can increase diversification of single banks and support their resilience to shocks, and may slow down contagious default. However, merger activities can also decrease stability if, for example, the network is driven into the contagion window or insufficiently stable banks emerge in key positions in the network.
urn:nbn:de:101:1-2023112813533677892334
Keywords: G01; G21; 330; Financial network model; Mergers and Acquisitions; Financial Stability; Contagion